Social anxiety symptoms, heart rate variability, and vocal emotion recognition in women: evidence for parasympathetically-mediated positivity bias. Issue 3 (4th May 2021) - Madison, Annelise; Vasey, Michael; Emery, Charles F.; Kiecolt-Glaser, Janice K.
ABSTRACT : Background and Objectives: Individuals with social anxiety disorder show pronounced perceptual biases in social contexts, such as being hypervigilant to threat and discounting positive social cues. Parasympathetic activity influences responses to the social environment and may underlie these biases. This study examined the associations among social anxiety symptoms, heart rate variability (HRV), and vocal emotion recognition. Design and Method: Female undergraduate students ( N = 124) self-reported their social anxiety symptoms using the Social Anxiety Disorder Dimensional Scale and completed a computerized vocal emotion recognition task using stimuli from the Ryerson Audio-Visual Database of Emotional Speech and Song stimulus set. HRV was measured at baseline and during the emotion recognition task. Results: Women with more social anxiety symptoms had higher emotion recognition accuracy ( p = .021) and rated positive stimuli as less intense ( p = .032). Additionally, although those with greater social anxiety symptoms did not have lower resting HRV ( p = .459), they did have lower task HRV ( p = .026), which mediated their lower positivity bias and greater recognition accuracy. Conclusions: A parasympathetically-mediated positivity bias may indicate or facilitate normal social functioning in women. Additionally, HRV during a symptom- or disorder-relevant task may predict task performance and reveal parasympathetic differences that are not found at baseline.